1992
DOI: 10.1017/s0022215100119516
|View full text |Cite
|
Sign up to set email alerts
|

Nasal teeth

Abstract: Ectopic and supernumerary teeth occur in a wide variety of sites. Those that have been reportedinclude the mandibular condyle, coronoid process, orbit, palate, nasal cavity and the maxillaryantrum. Eruption of teeth into these sites is rare, and easily overlooked. We present two casesin which eruption of teeth into the nose and paranasal sinuses was associated with significant morbidity and show how this was relieved by appropriate surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 4 publications
(2 reference statements)
0
28
0
1
Order By: Relevance
“…4 The nasal fossa is one of several sites in which ectopic teeth may be found. [3][4][5]8 In many cases no aetiological factors can be identified. 4,8 In 1979 Smith et al 8 identified 27 we l l -d o c u m e n t e d cases of intranasal teeth.…”
Section: Discussionmentioning
confidence: 99%
“…4 The nasal fossa is one of several sites in which ectopic teeth may be found. [3][4][5]8 In many cases no aetiological factors can be identified. 4,8 In 1979 Smith et al 8 identified 27 we l l -d o c u m e n t e d cases of intranasal teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic and supernumerary teeth may be present in many regions of maxillofacial skeleton. Commonly seen in palate and maxillary sinus, they have also been reported in nasal cavity, orbit, mandibular condyle, coronoid process, 1 facial skin, ethmoid sinus 2 and as teratomas in ovary, testes, anterior mediastinum and presacral regions. 3,4 The conditions commonly associated with increased prevalence of ectopic teeth include cleft lip and palate, cleidocranial dysplasia and Gardner syndrome.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding to the literature the genetic factors, odontogenic or rinogenic infection, trauma, dentigerous cysts and developmental defects like cleft palate are considered as aetiology of ectopic teeth even if its pathogenesis is consented as unknown (3). Ectopic teeth have been usually observed in dental and oral sites but rarely described in the mandibular condyle, coronoid process, orbit, palate, nasal cavity, nasal septum, chin and the maxillary antrum (4,5). Contrary, dental impressions or affections may be commonly seen within the maxillary sinus (6).…”
Section: Introductionmentioning
confidence: 99%
“…They are usually formed as a result of longterrm migration of endodental prothesis into the sinus cavity or uncontrolled application of tooth filling. The ectopic tooth eruptions in maxillary sinus reported in literature are usually run across incidentally during routine radiological evaluation but they are also rarely coincident with maxillary inflammation causing chronic sinusitis (4,5,7). In present study, a case of a 46-year-old woman with an ectopic maxillary third molar tooth, which presented in the right maxillary sinus with purulent rhinorrhea was described with a review of the related literature.…”
Section: Introductionmentioning
confidence: 99%